Wearable Self‐Charging Power Textile Based on Flexible Yarn Supercapacitors and Fabric Nanogenerators. Issue 1 (5th November 2015) - Pu, Xiong; Li, Linxuan; Liu, Mengmeng; Jiang, Chunyan; Du, Chunhua; Zhao, Zhenfu; Hu, Weiguo; Wang, Zhong Lin
Abstract : A novel and scalable self‐charging power textile is realized by combining yarn supercapacitors and fabric triboelectric nanogenerators as energy‐harvesting devices.